Temperature Effects on the Friction and Wear Behaviors of SiCp/A356 Composite against Semimetallic Materials - Like Pan; Jianmin Han; Zhiyong Yang; Jialin Wang; Xiang Li; Zhiqiang Li; Weijing Li (Advances in Materials Science and Engineering)
Due to the low density and high temperature resistance, the SiCp/A356 composites have great potential for weight reduction and braking performance using the brake disc used in trains and automobiles. But the friction coefficient and braking performance are not stable in the braking process because of temperature rising. In this paper, friction and wear behaviors of SiCp/A356 composite against semimetallic materials were investigated in a ring-on-disc configuration in the temperature range of 30°C to 300°C. Experiments were conducted at a constant sliding speed of 1.4 m/s and an applied load of 200 N. Worn surface, subsurface, and wear debris were also examined by using SEM and EDS techniques. The third body films (TBFs) lubricated wear transferred to the third body abrasive wear above 200°C, which was a transition temperature. The friction coefficient decreased and weight of semimetallic materials increased with the increase of temperature and the temperature had almost no effect on the weight loss of composites. The dominant wear mechanism of the composites was microploughing and slight adhesion below 200°C, while being controlled by cutting grooves, severe adhesion, and delamination above the 200°C.